2013
DOI: 10.5585/remark.v12i2.2507
|View full text |Cite
|
Sign up to set email alerts
|

I Saw it in the Movies, But Does That Matter? Product Placement in a Cross Cultural Study Between Brazil and the USA

Abstract: The broader objective of this study was to measure the attitudes of consumers regarding the brand displayed by this strategy as well as to highlight recall, recognition and purchase intentions generated by product placement on consumers from both Brazil and the USA. Cronbachs Alpha Coefficient ensured the reliability of survey instruments. The study involved the use of the Structural Equation Modeling (SEM) for the hypothesis testing. This study used the Confirmatory Factor Analysis (CFA) to assess both the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
3
0
3
Order By: Relevance
“…En referencia a la primera, el emplazamiento propiamente dicho es el más rentable: se trata de la colocación de un producto/marca en el atrezzo de la película, a partir de un intercambio económico o colaborativo entre la producción fílmica y la empresa o entidad generadora del producto/marca (Arconada, 2007;Boeing, Torres & Gentry, 2013). En estos casos, el objeto publicitado es fácilmente perceptible para el espectador, aunque no es consciente del mensaje publicitario.…”
Section: Estado De La Cuestiónunclassified
“…En referencia a la primera, el emplazamiento propiamente dicho es el más rentable: se trata de la colocación de un producto/marca en el atrezzo de la película, a partir de un intercambio económico o colaborativo entre la producción fílmica y la empresa o entidad generadora del producto/marca (Arconada, 2007;Boeing, Torres & Gentry, 2013). En estos casos, el objeto publicitado es fácilmente perceptible para el espectador, aunque no es consciente del mensaje publicitario.…”
Section: Estado De La Cuestiónunclassified
“…Films are a source of popular entertainment and a powerful promotional vehicle for products and behaviors [ 1 , 2 ]. Studies in Europe [ 3 6 ], the United States (US) [ 7 9 ], India [ 10 ], and Mexico [ 11 , 12 ] have found that exposure to onscreen film smoking promotes adolescent smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Essa nova forma da comunicação, conhecida no Brasil erroneamente como merchandising, merchandising comercial (Boeing, Urdan, & Gentry, 2013), merchandising televisivo (Trindade, 2007) ou de merchandising editorial (Blessa, 2009), que na verdade está focada na promoção de produtos e serviços nos próprios pontos de vendas (Shimp, 2002), é chamado de brand placement ou product placement e definida como sendo a inclusão paga de marcas de produtos ou de identificadores das marcas através de meios visuais e/ou sonoros na programação da mídia de massa (Karrh, 1998).…”
Section: Referencial Teóricounclassified
“…Por fim, questões éticas e morais podem ser mais facilmente indagadas devido à natureza do placement do que à propaganda tradicional (Andriasova, 2006 (Eisend, 2009) ou ainda ser semelhante em culturas um tanto diferentes no que se refere às atitudes e intenção de compra da marca inserida na mídia (Boeing et al, 2013).…”
Section: Referencial Teóricounclassified